Welding handbook - O'Brien, Annette (American Welding Society, 2004)
Vol.2 Part 1: 1- Arc welding power sources. 2- Shielded metal arc welding. 3- Gas tungsten arc welding. 4- Gas metal arc welding. 5- Flux cored arc welding. 6- Submerged arc welding. 7- Plasma arc welding. 8- Electrogas welding. 9- Arc stud welding. 10- Electroslag welding. 11- Oxyfuel gas welding. 12- Brazing. 13- Soldering. 14- Oxygen cutting. 15- Arc cutting and gouging. : Vol.3 Part 2: 1- Resistence spot and seam welding. 2- Projection welding. 3- Flash and upset welding. 4- Resistence welding equipment. 5- High-frequency welding. 7- Friction stir welding. 8- Ultrasonic welding. 9- Explosion welding. 10- Adhesive bonding. 11- Thermal spraying and cold spraying. 12- Diffusion welding and diffusion brazing. 13- Electron beam welding. 14- Laser beam welding, cutting and associated processes. 15- Other welding and cutting processes.